2020
DOI: 10.1136/jech-2019-213289
|View full text |Cite
|
Sign up to set email alerts
|

Association between C reactive protein and all-cause mortality in the ELSA-Brasil cohort

Abstract: BackgroundHigh-sensitivity C reactive protein (hsCRP) has been proposed as a marker of incident cardiovascular disease and vascular mortality, and may also be a marker of non-vascular mortality. However, most evidence comes from either North American or European cohorts. The present proposal aims to investigate the association of hsCRP with the risk of all-cause mortality in a multiethnic Brazilian population.MethodsBaseline data (2008–2010) of a cohort of 14 238 subjects participating in the Brazilian Longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 40 publications
2
15
0
2
Order By: Relevance
“…A study using the China Longitudinal Study of Health and Retirement (CHARLS) showed that plasma CRP was a predictor of all-cause mortality in the middle-aged and elderly population in China ( 19 ). A cohort study in Brazil also reached the same conclusion ( 20 ). Meta-analysis showed that CRP levels were associated with all-cause mortality in patients with type 2 diabetes and the risk of cardiovascular mortality was higher ( 21 ).…”
Section: Introductionsupporting
confidence: 58%
“…A study using the China Longitudinal Study of Health and Retirement (CHARLS) showed that plasma CRP was a predictor of all-cause mortality in the middle-aged and elderly population in China ( 19 ). A cohort study in Brazil also reached the same conclusion ( 20 ). Meta-analysis showed that CRP levels were associated with all-cause mortality in patients with type 2 diabetes and the risk of cardiovascular mortality was higher ( 21 ).…”
Section: Introductionsupporting
confidence: 58%
“…Inflammation can lead to abnormal bone marrow function, resulting in poor efficiency of red blood cell production, and also affects RBC membrane permeability, which causes reticulocytes to enter the peripheral blood circulation, and increases the proportion of immature RBC, leading to an increase in RDW [ 26 ]. Inflammatory markers are associated with mortality and major adverse CV events [ 27 , 28 ]. Therefore, RDW may be used as an indicator of mortality prediction.…”
Section: Discussionmentioning
confidence: 99%
“…This study lacked the adjustment of some unmeasured confounding factors, such as iron, folate, vitamin B12 and other nutritional information. Fifthly, this study did not collect information of inflammatory biomarkers such as C-reactive protein [ 27 ], procalcitonin [ 45 ] or interleukin-6 [ 28 ], as these biomarkers were not checked in most of our study subjects. Finally, this study only discussed baseline RDW on admission, and did not include subsequent changes in RDW for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Недавно опубликованные результаты бразильского исследования выявили достоверную связь вчСРБ со смертностью от всех причин в многомерной модели [14].…”
Section: Discussionunclassified